Analisis Business Continuity Management Media Informasi Kabupaten Tuban Menggunakan Standar ISO 22301 - Maulidina Rahmawati Surya; Pratiwi Susanti; Muhammad Bachtyar Rosyadi (Institut Teknologi Adhi Tama Surabaya, 2026)
Information media systems constitute a crucial component of public information services. Disruptions to the infrastructure supporting these systems can halt public services and trigger the spread of disinformation. This study aims to analyze and design a Business Continuity Management (BCM) system for Tuban Regency's information media, based on the ISO 22301 standard. A qualitative research approach was employed, utilizing observation, interviews, and risk analysis via Business Impact Analysis (BIA). The analysis identified several critical threats, such as cyberattacks, hardware failures, and power outages. The study concludes with recommendations for a disaster recovery strategy and standard operating procedures to ensure the continued availability of Tuban Regency's information media services during a crisis.